Deep Learning - Recent Findings and Research - Manuel Jesus Domínguez-Morales; Javier Civit-Masot; Luis Muñoz-Saavedra; Robertas Damaševičius (IntechOpen, 2024)
Deep learning has revolutionized numerous fields due to its ability to process vast amounts of data and learn complex patterns. Its importance lies in its capacity to tackle tasks that were difficult or impossible for traditional algorithms. In health care, for example, it aids in diagnosing diseases. In finance, it improves fraud detection and stock market predictions. Moreover, it enhances natural language processing, enabling better machine translation and chatbot interactions. It also fuels advancements in autonomous vehicles and robotics. Its adaptability and efficiency make it indispensable in today's data-driven world, optimizing processes and driving innovation across multiple domains.This book provides a comprehensive overview of deep learning, examining its principles and growing importance in all aspects of life.